Peran Komisaris Independen dalam Mewujudkan Good Corporate Governance di Perusahaan Publik - Badriyah Rifai (Fakultas Hukum Universitas Islam Indonesia, 2009)
The existence of independent commissioner is aimed to set up climate which is more objective, and independent as well as to keep fairness and to give balance berween the interest of majority share holders and the proctection of interest of minority share holders, even the interes of other stakeholders. Independent commissioner is very needed bt the exiting companies in Indonesia, particulary for public companies. With the existence of independent commissioner, all the concern parties have great benefit, especially through the establishment of condition which is suitable with the principle of Good Corporate Governance, where independent commissioner can give opinion with the higher level of independence and accountabilityKeywords: : independent comissioner, good corporate governance